A Comparative Study of Administrative Corruption Identification in Islamic Sharia, International Documents and Afghanistan’s Legislative Documents - Muhammad Yousuf, Zamani; Sharifullah, Amin; Shahidullah , Safi (Integrated Journal for Research in Arts and Humanities, 2022)
The aim of this research is that to compare the nature of Administrative corruption in Islamic law international documents and the Afghanistan’s legislative documents. To see if these legal systems have similar or different positions in this issue. If similar, what would be the reason? If different, what would be the reason? And for what reasons would be prefer one over the others? We used library method for research and collected materials from reliable resources, after analysis, we concluded that the nature of Administrative corruption in Islamic sharia, international documents and Afghanistan’s legislative documents have different definitions, the reason for which is the different conditions prevailing in different societies and the different reactions of peoples to them, because corruption is a social phenomenon and occurs in society It was also concluded that the nature of corruption is prevalent in Islamic legal system than the other two, because it is definition is broader and comprehensive than the other two. It is comprehensive because it includes public, private and mixed institutions, as well as every wrongdoing, whether it is large or small, is covered and cannot be left out. Time is of the essence, whether it is the accepted forms of corruption in today's advanced 7th century and if it becomes known in the future, it will cover all, and ultimately, the status of heads up whether it's superior or inferior. But the definitions of the nature of corruption in international documents and in the legislative documents of Afghanistan do not have all these advantages, but by the way have the problems, about which comprehensive information is included in the research material can be read there.